Strategic Management of Early Education Section and Islamic Boarding Schools in Improving Managerial Competence of The Principal of Education Equality in Salafiyah Islamic Boarding Schools (PKPPS) at Kabupaten Bekasi - Yuniarto, Evan; Suharyat, Yayat; Diyah (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
This study aims to find out and analyze how the strategic management of the Diniyah Education and Islamic Boarding School sections in improving the managerial competence of the head of the Equality Education madrasah at the Salafiyah Islamic Boarding School (PKPPS) throughout Bekasi Regency